A Visionary Working Model for Pursuing Social Justice Praxis Through Educational Psychology Courses. (April 2023) - Mustafaa, Faheemah N.; Martinez, Mayra Nuñez
Introduction: We propose a visionary working model to normalize the pursuit of social justice praxis in educational psychology courses. Using our undergraduate course as an example, we discuss our roles as instructors, curriculum, and pedagogical strategies for forward progress. Statement of the Problem: Despite stated commitments to diversity, equity, and inclusion as integral to psychology research and practice (e.g., American Psychological Association statements), most educational psychology courses are highly theoretical and do not prepare learners to counter social injustices in praxis that are meaningful for the global majority. Literature Review: We make the case for why educational psychology courses are ideal for training students for social justice praxis, and outline how diversity, equity, and inclusion strategies in the literature can be used as levers. Teaching Implications: We provide assignment resources to illustrate how instructors can begin to integrate diversity, equity, and inclusion throughout a course to co-construct more just futures. Conclusion: Actualizing this visionary model of normalizing social justice praxis in educational psychology courses requires multi-level supports at global and local levels. Using case studies to address complex social injustices within an engaged teaching and learning environment has significant potential to empower and prepare learners to forward social justice.